Impact of Mindfulness-Based Stress Reduction Techniques on General Well-Being of Employees Working on a Behavioral Health Unit - Clyde R. Smith; Abhishek Rai; Jaspreet Brar; Avianna Castro (Indian Journal of Integrative Medicine, 2021)
Background: Mindful-based Stress Reduction (MBSR) interventions have become a breakthrough treatment modality inreducing stress and improving overall general well-being. MBSR practiced by individuals gets impacted on a physical, social,mental, emotional, and spiritual level. MBSR approaches have been studied and support to improve the general wellbeing ofindividuals and enhance the quality of life. Methods: Behavioral Health employees participated in daily independent mindfulbasedstress reduction sessions over six weeks. The mindfulness audio files are recorded specifically for this research project.Employees completed a demographic form, Perceived Stress Scale (PSS), and Subjective Happiness Scale (SHS) pre-andpostsix-week period. The PSS and SHS were used to complete and collect qualitative data on the effectiveness of MBSR.Results: This study reported the following results. A total of 22 behavioral health employees volunteered to participate in thestudy. The average score pre-study on SHS was (16.41+2.45). Post mindfulness intervention, the average score on SHSincreased to (18.71+2.49). The average score pre-study on PSS was (20.18+3.17) post mindfulness intervention the averagescore in PSS came down to (10+4.29). The results were highly significant. Conclusion: The results suggest a high correlationwith a reduction in behavioral health employees’ perceived stress and physical response to stress in their personal andprofessional life when individuals practice MBSR techniques. Reduction in perceived stress of mental health workers resultsin the improved general wellbeing of the employee and improve capabilities for the employee to handle stress at work,therefore, improving patient care outcomes.